(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Recently, the increase in environmental pollution has been studied by researchers, especially the increase in abnormalities and blood level in aquatic organisms. In this regard, one of the reasons is the presence of plastic causes that are often found in water. The existence of plastic waste in the water is divided into 3 categories, namely macroplastic (>25 mm), mesoplastic (5-25 mm), and microplastic (<5 mm). Microplastics occur from the degradation of macroplastics and mesoplastics in waters. Microplastics in lakes, rivers, and estuaries cause a stress response in the bodies of aquatic organisms including dumbo catfish (Claries gariepinus). The stress response of fish can be seen in the changes in blood components and levels of blood, which are used to determine the condition or health status of fish by counting the number of erythrocytes, leucocytes, hemoglobin, and differential leucocytes. This study aims to analyze the stress response of dumbo catfish caused by microplastic exposure to hematology. This used research method was a completely randomized design (CRD) with one factor and three treatment levels. The results showed that the increase in rearing time was from 0 to 30 days and varied of doses mixture commercial fish feed and microplastic. The results showed the highest erythrocyte value of 2.78(x106) cell/mm3 in 15 days of rearing time by adding mixed commercial feed and microplastics of 15%.